Influence of Sodium Hydroxide Concentration and Soaking Duration on Absorbency and Weight of Tencel Fabric During Mercerization - Putra, Rafly Prahmantia; Komalasari, Maya; Luciana, Luciana (Sainteks: Jurnal Sain dan Teknik, 2025)
Tencel fabric has characteristics similar to cotton fibers but possesses the durability of synthetic fibers. It is produced using environmentally friendly technology. Tencel is made with the solvent NMMO (N-methylmorpholine-N-oxide), which is recyclable up to 99%. This fabric is derived from cellulose fibers or regenerated cellulose fibers. The advantages of tencel include good absorbency, luster, and tensile strength. This study aims to determine the optimal concentration of caustic soda (sodium hydroxide) and soaking time in the mercerization process during the finishing preparation of tencel fabric, focusing on weight reduction, absorbency, tensile strength, dimensional stability, and fiber morphology. Tencel is known for its easy fibrillation in wet conditions and significantly high tensile strength. Previous studies have shown that alkali treatment can enhance absorbency and luster. Mercerization was carried out with variations in caustic soda concentration at 7, 9, 11, and 13 °Be and soaking times of 30, 45, and 60 seconds. The results showed that higher caustic soda concentrations and longer soaking times led to decreases in weight, tensile strength, and dimensional stability. However, absorbency increased up to a certain concentration before declining again. This is also influenced by changes in fiber morphology due to the mercerization process using caustic soda. The optimum point was determined using a ranking and weighting method based on test results and evaluation of tencel fabric. The optimal mercerization condition was found at a caustic soda concentration of 9°Be with a soaking time of 45 seconds, yielding a weight reduction of 4.07%, absorbency of 4.5 cm/2 minutes, warp direction tensile strength of 6.34 N and weft direction of 7.5 N, and dimensional stability of 6.8% in the warp direction and 2.4% in the weft direction.